Reformulation of Narcotics Regulations to Eliminate Inconsistent Interpretation for Narcotics Offenders - Anita Zulfiani; Hartiwiningsih; Dian Esti Pratiwi; Yussri Sawani (Jurnal Hukum dan Peradilan, 2026)
A considerable number of correctional facilities and detention centres in Indonesia are currently grappling with overcrowding issues, primarily driven by inmates involved in narcotics-related cases. This research aims to investigate the inconsistencies within narcotics regulations that lead to diverse interpretations of the law by law enforcement officials. The pressing aim of this study is to reduce the population of narcotics offenders serving prison sentences, thus alleviating the problem of overcrowding. This research adopts a qualitative methodology focusing on legislative and conceptual analysis. The research findings underscore the necessity for a revision of narcotics legislation. More specifically, this involves categorizing narcotics offenders based on their intent, making a clear distinction between "narcotics users," encompassing individuals who use drugs, suffer from addiction, or have become victims of narcotics abuse, and "narcotics profiteers," which includes those engaged in selling, facilitating transactions, manufacturing, or inducing others into narcotics abuse and victimization. In summary, this research highlights that consistency is needed in the regulation of narcotics articles by creating clear categories of behavior that are included in narcotics crimes to eliminate the various interpretations of the law, ultimately ensuring a fair and legally certain criminal justice system.